Kontribusi Usahatani Kelapa Terhadap Pendapatan Keluarga Petani di Desa Tammerodo Utara Kecamatan Tammerodo Sendana Kabupaten Majene - Safitri, Nur; Arhim, Muhammad; Dahniar; Alim, Nurmaranti (Pangale Journal of Forestry and Environment, 2021)
Tammerodo Utara village has a land area of about 571 hectares. The main profession of the community is farmers, especially coconut farmers. In addition, there are various other kinds of farming carried out by the community such as clove farming, banana farming and so on. But some people besides working as farmers but also have businesses that are not included in the agricultural sector. The problem that is being studied in this research is how the driving and inhibiting factors that affect the amount of coconut production produced by farmers, which then affects how much coconut farming contributes to farmers’ household income. This study aims to analyze the contribution of coconut farming to the household income of farmers in Tammerodo Utara Village, Tammerodo Sendana District, Majene Regency. The population in this study was 279 coconut farmers, with a total sample of 15 % or 42 respondents. Data collection techniques using the method of obsevation, interviews, questionnaires, and documentation. The data analysis method used is descriptive analysis method and farm business analysis. Based on the result of the study, it is known that the average contribution of coconut farming to the total income of farmer households in Tammerodo Utara Village, Tammerodo Sendana District, Majene Regency is 26,1 %. So it can be concluded that coconut farming is a source of income that contributes quite well to the total household income of farmers.